The Effect of Cultivation Media on Matriconditioning Technique and the Concentration of Onion Peel Waste PGR on the Viability and Yield Rice (Oryza sativa) Through the Metabolic Activity of the Seed - Amany, Alfiyyah Nur; Setiyono, Setiyono; Sholikhah, Ummi; Ratnasari, Tri; Meliala, Susan Barbara Patricia Sembiring; Arum, Ayu Puspita; Savitri, Dyah Ayu (Green Engineering Society, 2025)
A major limiting factor for rice production in the tropics is the decline in seed quality due to storage duration and environmental conditions. Rice seeds are often stored for extended periods, making seed expiration unavoidable. Expired seeds frequently undergo quality deterioration. Therefore, an effective approach is needed to mitigate quality decline and sustain rice production. This study aims to evaluate the effectiveness of different matriconditioning techniques and various concentrations of onion peel waste-derived plant growth regulators (PGRs) in maintaining seed viability and rice yield. The research was conducted using a Completely Randomized Design (CDR) with a two-factor experimental setup and three replicates. The first factor was the matriconditioning medium, consisting of three levels: M1 (soil), M2 (soil + husk charcoal), and M3 (soil + husk ash). The second factor was the concentration of onion peel waste-derived PGR, consisting of four levels: K1 (0% – water), K2 (25% – 250 mL onion peel waste PGR per 1000 mL), K3 (50% – 500 mL onion peel waste PGR per 1000 mL), and K4 (75% – 750 ml onion peel waste PGR per 1000 mL). The results showed that matriconditioning with soil and husk charcoal, along with 25% onion peel waste-derived PGR, enhanced rice seed viability. Additionally, a 75% concentration of onion peel waste PGR significantly influenced the weight of 1000 grains and the total harvested grain weight.